PERKEMBANGAN ILMU DI DUNIA ISLAM KLASIK (ABBASIYAH) - Putri Rahma Dani; Amril Mansur (PT. Jurnal Center Indonesia Publisher, 2025)
Using a descriptive qualitative approach, this study aims to describe the development of science in the Classical Islamic world during the Abbasid Dynasty (750–1258 AD). Literature studies, interviews with Islamic historians, and observations at historical sites are the methods used. The results of the study show that science made rapid progress during the Abbasid era, especially in mathematics, medicine, astronomy, and chemistry. Translating and disseminating information from Greek, Persian, and Indian civilizations was greatly assisted by centers of knowledge such as Bayt al-Hikma (House of Wisdom) in Baghdad. Famous scientists such as Al-Khwarizmi, Ibn Sina, and Al-Razi made major contributions through their highly influential works, which were then widely disseminated in the West. In addition, this study found that the socio-political conditions and support from the Abbasid caliphs.